2020
DOI: 10.3389/fnhum.2020.551470
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Spatial Patterns of Intrinsic Brain Activity in Osteonecrosis of the Femoral Head: A Resting-State Functional Magnetic Resonance Imaging Study

Abstract: Objective: Osteonecrosis of the femoral head (ONFH) is a common condition that is encountered in clinical practice, and yet, little is known about its characteristics and manifestations in the brain. Therefore, in this study, we aimed to use resting-state functional magnetic resonance imaging (rs-fMRI) to investigate the spatial patterns of spontaneous brain activity in the brain of ONFH patients. Methods: The study included ONFH patients and healthy controls. The pattern of intrinsic brain activity was measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…In addition, functional and structural changes in the PFC, including ankylosing spondylitis ( Liu et al, 2020 ), irritable bowel syndrome ( Mao et al, 2020 ), chronic lower back pain ( Yu et al, 2020 ), and neuropathic pain ( Li et al, 2020 ), have been demonstrated in other pain studies. In a recent rs-fMRI study ( Feng et al, 2020 ), researchers revealed an abnormal pattern of brain activity in ONFH patients and found that the most significant increase in ALFF occurred in pain-related brain regions, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, functional and structural changes in the PFC, including ankylosing spondylitis ( Liu et al, 2020 ), irritable bowel syndrome ( Mao et al, 2020 ), chronic lower back pain ( Yu et al, 2020 ), and neuropathic pain ( Li et al, 2020 ), have been demonstrated in other pain studies. In a recent rs-fMRI study ( Feng et al, 2020 ), researchers revealed an abnormal pattern of brain activity in ONFH patients and found that the most significant increase in ALFF occurred in pain-related brain regions, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, joint dysfunction was confirmed to elicit changes in brain function ( Di Russo et al., 2006 ). In one study with a small patient cohort, abnormal patterns of brain activity were observed in ONFH patients ( Feng et al, 2020 ). Consequently, we hypothesized that there might be changes in neural plasticity that are associated with ONFH.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, MRI is the most sensitive imaging modality for early-stage osteonecrosis. The characteristic appearances of osteonecrosis on MRI shown as Figure A9 may include: i) a serpentine band of low-signal intensity rim on T1-weighted images (T1WIs), ii) an inner high-signal-intensity band and an outer low-signal-intensity band are visible (so-called double-line sign) on T2-weighted sequences (T2WIs) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The determination of whether the femoral head collapses and the degree of articular cartilage collapse is an important guiding basis for clinical treatment [ 7 , 8 ]. Therefore, imaging is often used in clinical examination and prediction, among which CT and X-ray scanning are commonly used [ 9 ]. X-ray scanning, as one of the conventional methods for the diagnosis of ONFH, mainly reflects the results of disease examination by the tissue absorption rate of the X-ray; however, it is not sensitive to the early lesions of ONFH [ 10 ].…”
Section: Introductionmentioning
confidence: 99%